Carotenoderma in teenagers. - Baldassari, L. (European Journal of Pediatric Dermatology, 2018)
Carotenoderma is a yellow pigmentation of the skin due to increased plasma level of betacarotene. Four cases of carotenoderma observed in the last three years in girls aged 14 to 18 are reported. The skin discoloration ranging from yellow to orange was particularly visible on the nasolabial folds, the perioral and the palmar and plantar region. In order to keep fit, all the teenagers followed a strict vegetarian diet, which was responsible for significant weight loss. The permitted foods were prevalently oranges, mandarins and carrots, all containing high quantities of carotenoids. Blood examinations showed significantly increased plasma levels of plasmatic betacarotene. Two girls had been already diagnosed as having an anorectic syndrome. The other two girls underwent a psychiatric counselling, which put in evidence a hysterical syndrome with anorectic traits. Carotenoderma may be occasionally observed by dermatologists. Therefore, dermatologists should be aware that carotenoderma may follow in some girls erroneous slimming diets. Carotenoderma can be also a clue to the diagnosis of a true psychiatric disorder.